Test-Taking Skills in College Students With and Without ADHD. (February 2013) - Lewandowski, Lawrence; Gathje, Rebecca A.; Lovett, Benjamin J.; Gordon, Michael
College students with attention deficit hyperactivity disorder (ADHD) often request and receive extended time to complete high-stakes exams and classroom tests. This study examined the performances and behaviors of college students on computerized simulations of high-stakes exams. Thirty-five college students with ADHD were compared to 185 typical peers on measures of reading decoding, speed, vocabulary, comprehension, test strategies, time management, and test anxiety. Results indicated no differences between students with and without ADHD on various reading (decoding, speed, vocabulary, and comprehension) and test-taking variables (time utilization, navigation style, or strategy use), yet significant differences were present regarding their perceptions of, and anxiety during, test taking. It appears that students with ADHD perform similarly to peers on timed reading tests, although they think they perform less well and worry more about their performance.